Comunicazione autorevole e disintermediazione. Mutazioni prossemiche del post-pandemia - Pier Paolo Bellini (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The pandemic has not only affected our bodies (biological dimension) and our minds (psychological dimension): it has also left a profound mark in our relationships (social dimension). Daily life in lock down seems to be a distant and now faded memory, even if a few months have passed since we were barricaded in our homes: yet certain habits have been, perhaps irrevocably, changed. It is our intention to try to identify these micro-traumas that have occurred at the level of communication practices in this last year and a half in order to be able to interpret them as traces of new possible social configurations: that is, we want to reflect on the turmoil that has occurred in daily interactions between people, between systems and between people and systems and hypothesize their possible developments on some essential aspects of social and, more specifically, communicative relationships. In particular, it is useful to focus our attention on two aspects of our daily life that have suffered an attack (almost in a chemical sense), proposing new reasons of high criticality and uncertainty to the already complex postmodern life: on the one hand (the macro-social one), the authority / credibility of the information sources, on the other hand (the micro-social one), the management of spaces and communication channels.